IMPLEMENTASI PROGRAM BEASISWA TI BUPATI (BESTI) OLEH PEMERINTAH DAERAH KABUPATEN BANDUNG - , Widdy Yuspita Widiyaningrum; , Fachira Salsabila (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2024)
This study aims to analyze the regent scholarship program (BESTI). The provision of the ti bupati scholarship (BESTI) aims to help ease the burden of tuition fees for students or students in pursuing undergraduate education (S1) with a UKT of Rp. 5,000,000 per semester. The provision of scholarships is carried out by the people’s welfare sector of Bandung Regency to help underprivileged and outstanding students or students by fulfilling the requirements and policies provided by the Bandung Regency government with the condition of memorizing at least 1 juz Al-Qur’an and domiciled in Bandung Regency. This research uses descriptive qualitative methods with data collection techniques through interviews, observation, and documentation. The research uses Edward III’s theory, namely communication, resources, disposition and bureaucratic structure. The results showed that the implementation of the Regent’s Scholarship Program (BESTI) has been running quite well as seen from the existence of good communication patterns, disposition and a clear bureaucratic structure. As for the obstacles and shortcomings in implementation, in this case it concerns the lack of maximum empowerment of government officials, especially those in charge of the Regent’s Scholarship Program (BESTI), starting from the lack of Human Resources to the existence of a budget that is considered still unable to meet service needs.